Prevalence, indications and appropriateness of antiplatelet therapy in patients operated for acute aortic dissection: associations with bleeding complications and mortality. Issue 2 (9th October 2012) - Hansson, Emma C; Dellborg, Mikael; Lepore, Vincenzo; Jeppsson, Anders
Abstract : Objective: To assess the prevalence, indications and appropriateness of antiplatelet therapy in patients operated for acute aortic dissection and its associations with bleeding complications and mortality. Design: A retrospective single-centre study comparing patients with and without ongoing antiplatelet therapy. Setting: University Hospital in Western Sweden. Patients: 133 consecutive patients operated during 2007–2011. Interventions: All patients were operated for acute aortic dissection type A. Main outcome measures: Indication and appropriateness of antiplatelet therapy; perioperative bleeding complications, transfusions and mortality. Results: 43 of 133 patients (32%) had ongoing platelet inhibition at the time of surgery, 19 (14%) with acetylsalicylic acid (ASA) alone and 24 (18%) with ASA and clopidogrel. Unspecific chest pain and ST depression were the most common indications (42% and 23%, respectively). 2.3% had ST elevation and 12% had elevated biomarkers for myocardial injury. Only 29% of the patients with dual antiplatelet therapy had appropriate treatment according to current guidelines. Patients with ongoing platelet inhibition had significantly larger intraoperative (1800 (IQR 950–4250) vs 800 ml (500–2500), p=0.010) and postoperative bleeding volumes (800 (420–1605) vs 500 ml (390–1070), p=0.037). 30-day mortality in patients on dual antiplatelet therapy was 30.4% compared with 13.0% in patients with no or single antiplatelet therapy (p=0.038). Conclusions: The indication for immediate antiplatelet therapy in patients later operated for acute aortic dissection was weak or absent in the majority of cases. Patients with ongoing platelet inhibition had more bleeding complications. Dual antiplatelet therapy was associated with increased early mortality.